SISTEM INFORMASI DOSEN UNIKS ONLINE - Harianja Harianja (Universitas Islam Kuantan Singingi, 2019)
Uniks is one of institute in Indonesia has around one hundred lecturers or educators. The educator is the pioneer in the university to do caturdharma Uniks and become measurement in assessment the performance of Uniks. Certainly, Uniks have to publish caturdharma activities from the lecturers, cause the society still unknown about the caturdharma activities. The aim of this research is to built the informations system of Uniks’ lecturers to publish all of the caturdharma activities.